Characterization and Evaluation of the Efficiency of Organic Amendments and Native Macrophytes for the Treatment of Acid Mine Drainage in Hualgayoc—A Case Study. - Nuñez-Bustamante, Ever (2025)
Acid mine drainage (AMD) is a major environmental issue due to its high heavy metal concentrations and low pH, posing risks to ecosystems and human health. In Hualgayoc, Cajamarca, Peru, AMD contamination from mining activities necessitates effective remediation strategies. This study evaluated the removal efficiency of organic amendments, municipal waste compost (MWC), cattle manure compost (CMC), vermicompost (HMS), corn stalk biochar (CSB), sludge biochar (SLB), pine biochar (PBC), and native macrophytes Carex pichinchensis (CAX), Juncus ecuadoriensis (JSP), and Myriophyllum aquaticum (MYA) in removing As, Cd, Cu, Fe, and Zn. A physicochemical characterization of AMD, amendments, and plants was conducted, and sorption capacity was determined through triplicate analyses. The results showed that SLB achieved a 100% Zn removal, while CSB removed over 90% of Cu and Fe. Among the organic amendments, CMC demonstrated the highest As and Cd removal (~100%). Regarding macrophytes, CAX achieved a ~97% Fe removal, and MYA exhibited Cd affinity. CSB had the highest sorption capacity for Cu (0.139 mg/g), Fe (1.942 mg/g), and Zn (0.149 mg/g), highlighting its potential for metal remediation. Organic amendments enhanced metal adsorption and stabilization, outperforming macrophytes in heavy metal removal. Combining organic amendments with native plants is recommended to assess their synergistic potential for AMD remediation.